Impact of Myocardial Bridge on Life‐Threatening Ventricular Arrhythmia in Patients With Implantable Cardioverter Defibrillator - Kozo Okada; Kiyoshi Hibi; Yutaka Ogino; Nobuhiko Maejima; Shinnosuke Kikuchi; Hidekuni Kirigaya; Jin Kirigaya; Ryosuke Sato; Hidefumi Nakahashi; Yugo Minamimoto; Yuichiro Kimura; Eiichi Akiyama; et al. (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease, 2020)
Background Myocardial bridge (MB), common anatomic variant, is generally considered benign, while previous studies have shown associations between MB and various cardiovascular pathologies. This study aimed to investigate for the first time possible impact of MB on long‐term outcomes in patients with implantable cardioverter defibrillator, focusing on life‐threatening ventricular arrhythmia (LTVA). Methods and Results This retrospective analysis included 140 patients with implantable cardioverter defibrillator implantation for primary (n=23) or secondary (n=117) prevention of sudden cardiac death. Angiographically apparent MB was identified on coronary angiography as systolic milking appearance with significant arterial compression. The primary end point was the first episode(s) of LTVA defined as appropriate implantable cardioverter defibrillator treatments (antitachyarrhythmia pacing and/or shock) or sudden cardiac death, assessed for a median of 4.5 (2.2–7.1) years. During the follow‐up period, LTVA occurred in 37.9% of patients. Angiographically apparent MB was present in 22.1% of patients; this group showed younger age, lower rates of coronary risk factors and ischemic cardiomyopathy, higher prevalence of vasospastic angina and greater left ventricular ejection fraction compared with those without. Despite its lower risk profiles above, Kaplan–Meier analysis revealed significantly lower event‐free rates in patients with versus without angiographically apparent MB. In multivariate analysis, presence of angiographically apparent MB was independently associated with LTVA (hazard ratio, 4.24; 95% CI, 2.39–7.55; P<0.0001). Conclusions Angiographically apparent MB was the independent determinant of LTVA in patients with implantable cardioverter defibrillator. Although further studies will need to confirm our findings, assessment of MB appears to enhance identification of high‐risk patients who may benefit from closer follow‐up and targeted therapies.